Listening as ‘Guiding Tool’ in the Continuous Improvement of University Education: A Holistic Approach - Verna, Ida; Antonucci, Gianluca; Sargiacomo, Massimo; Venditti, Michelina (European Scientific Journal, ESJ, 2019)
The quality of higher education is linked to listening and to satisfying the needs of all those involved (social partners, teachers, students, institutional bodies). The satisfaction of these needs requires a holistic approach that is capable of respecting the complex nature of teaching. In this sense, an approach called L’Ascolto has been developed, aimed precisely at listening to the needs and satisfying those needs through the design, management, evaluation and improvement of a degree course and the individual subjects that compose it, considered as a system of relationships and interdependencies. The approach is based on the TQM logic where the satisfaction of needs is pursued through a holistic approach. Given the innovative nature of the L’Ascolto, it is initially introduced and subsequently developed both in reference to the principles and methods of operation as well as in relation to other existing models.